Analysis and Mitigation of Harmonics Distortion with Optimization Capacitor Banks and Single-Tuned Passive Filters - Reza Sarwo Widagdo; Kukuh Setyadjit; Izzah Aula Wardah (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2023)
Electrical system power supplies always require a completely sinusoidal voltage signal. But for a variety of reasons, utilities often struggle to maintain these desired conditions. Deviations of voltage and current waveforms from a sinusoidal form are called harmonic distortions. Harmonic distortions in power networks are increasing due to the widespread use of non-linear loads. In this article we will analysis at a single-tuned passive filter and optimization using a capacitor bank. Load-current analysis determines the efficiency of the filter application by calculating the load bus voltage and total harmonic distortion (THD). To simulate the work, the Electrical Transient Analyzer Program (ETAP) software was used. This system was created specifically for this simulation and does not represent a real system. This model tests the effects of injecting harmonic currents into a power grid through a variable speed drive (VFD). The filter is attenuated with a capacitor bank.